Sar Torah Prayer – From Magic and Liturgy to Visionary Literature: An Early Chapter in the Textual History of the Hekhalot Literature - Bar-Asher, Avishai (Jewish Thought, 2025)
This article is dedicated to the reconstruction and analysis of the “Sar Torah [Prince of Torah] Prayer”, a textual unit within the Hekhalot and Merkabah literature, which has not survived in its original form. The study focuses on a parchment scroll from the Geonic period, preserved in the Cairo Genizah (T.-S. K 21.95.S), one of the earliest extant documents of the Hekhalot literature. Based on a new decipherment of the text and a comparative analysis with the medieval textual witnesses of Hekhalot Rabbati, as well as other later documents, the article systematically reveals the scroll’s original role and placement: a sequence of passages of praise and prayer that originally formed part of the Prince of Torah ceremony, alongside the reading, the incantations of angels, and other magical acts. The first part of the article examines passages concerning the instructions for prayer and the hymns of praise accompanying the incantations, as preserved in the medieval textual witnesses of Hekhalot Rabbati. This analysis exposes fissures in the textual tradition and indicates traces of editorial activity that left the tradition fragmented. The second part is devoted to deciphering and reconstructing previously unreadable passages from the scroll, thereby clarifying the significance of a set of prayer passages that accompanied the magical acts in the Prince of Torah ceremony and were transmitted within the scroll. The third part surveys other later manuscript witnesses, which shed light on the dissemination and development of the prayer in diverse historical contexts. Finally, the fourth part summarizes the article’s main conclusions and emphasizes their importance for understanding the history of transmission of Hekhalot and Merkabah texts, particularly the early textual formation of Hekhalot Rabbati, as well as for elucidating the relationship between magic, prayer, the hymns of praise to God and the Merkava, and the visionary elements within this literature. An edition of the prayer from the Genizah is included in the appendix. The article’s findings pertain primarily to two domains. First, textual criticism: the Geniza scroll preserves an early configuration of a ritual-textual unit, which underwent significant transformation in form and sequence due to its incorporation into a new narrative and literary context, thus illuminating the stages of formation and editorial development of Hekhalot Rabbati. Second, the conceptual history: the editing and repositioning of the prayer in a literary context reflects a genre transition from a ritual-practical composition to a narrative anthology, shedding new light on the complex interplay between magic, prayer, and visionary elements in Hekhalot and Merkabah literature